Students’ Responses to The Use Of Information Technology (IT) In The English teaching-Learning at SMK Ma’arif 5 Gombong - Alek Andika (LPPM IAINU Kebumen, 2019)
The aimsof this research areto describe students’ responses and to know the substantive theoriesthat can be formulated from the reality of students’responses to the use of Information Technology (IT) in the English teaching-learning at SMK Ma’arif 5 Gombong. Type of research is a qualitative naturalistic with subjects X and XI grade students. The subjects of the research are students from multimedia, office administration, accounting and automotive study program of SMK Ma’arif 5 Gombong in academic year 2017/2018which consists of 30 students.The data were obtained from students directly in the class by using an open questionnaire. Data analysis techniques inthis researchcarried outbycategorical analysisand descriptiveanalysis.The results showed that there were 141students’responses which were divided into two major group consisted of 77 students’ positive responses and64 students’ negative responses. These all responses were broken down into 22 categories. Based on the descriptive data analysis, there were 5 prominent of students’ responses toward the use of IT in the English teaching learning. They were 3 positive responses in relation to process, method and material. Then, there were 2 negative responses in relation to physics and attitude. There were also obtained 5 substantive theories to the use of IT in the English teaching learning. They were 3 positivesubstantive theorieswhich explained that IT gave the effectiveness and efficiency, IT couldmake easier in getting English materialand IT couldimprove student’s learning outcomes. Then, there were 2 negative substantive theorieswhich explained that IT was able to cause a noisy learning process and IT made anuncomfortable learning processif IT was not prepared properly. On the basis of the results of this research showedthatthere were many advantages of the use of IT more than its disadvantages. Therefore, itcan be suggested for English teachersto use IT in their teaching-learning process